The aerodynamics of sailing apparel - Jansen, A.; van Deursen, B.; Howe, C. (Procedia Engineering, 2012)
The paper presents the effect of changes in sailing apparel on aerodynamic drag, starting from the assumption that drag reduction of sailing apparel will increase the speed of an Olympic class sailing boat (in this case the Laser, a single-handed Olympic dinghy), mainly on upwind courses. Due to the fact that literature on this specific subject is non-existent, a theoretical framework on hydrodynamic and aerodynamic drag of the sailing boat and sailor had to be set-up to provide us with ball park figures on the effect of changes in sailing apparel. It showed that the aerodynamic drag caused by the sailor was around 12% of the total drag (aerodynamic and hydrodynamic). This also demonstrated the room for improvement. Next, the actual aerodynamic drag of eight different combinations of state-of-the art sailing apparel was measured in the wind-tunnel (TUDelft Open Jet Facility) at various wind angles and wind speeds (up to 17 m/s). The experimental results were then compared to the results of the theoretical framework. The results of the experiment show a maximum difference of 11% in aerodynamic drag between the best and worst case scenario (at 8.2 m/s wind speed). This reduction of the sailors` aerodynamic drag is estimated to reduce the total (sailor + sailing boat) drag by 1.2%.